Knowledge and practices of doctors at the National Hospital of Sri Lanka on screening and management of alcohol misuse among patients - KC Nagodavithana; N Gunawardena (College of Community Physicians of Sri Lanka, 2012)
Introduction Problems related to alcohol misuse in Sri Lanka are on the rise. Early screening and structured interventions by doctors have been shown to make a significant diminution in alcohol misuse among patients. Objectives This study aimed to assess the knowledge and practices of doctors at the National Hospital of Sri Lanka on screening and management of alcohol misuse among patients. Methods This was a hospital based descriptive cross-sectional study. Doctors (n=385) of all designations attached to wards where patients with alcohol related problems are admitted, were assessed using a self-administered questionnaire. Factors associated with practices were assessed using cross tabulations and χ2 statistic. Results Response rate was high (91.4%). Respondents were mainly males (63.6%; n=224) in the age group of 25-34 years (48.0%; n=169). A majority were in the category of "medical officers" (39.4%; n=139) attached to general medicine or surgery units (49.7%; n=175) with work experience of <10 years (68.2%; n=240). A weighted score was developed for overall knowledge on screening and management. The proportion of doctors with "Good" overall knowledge was high (75.9%; n=267). However, only 53.4% (n=188) were aware of available standard screening tools. The majority (93.5%; n=329) of doctors were inquiring into alcohol habits of male patients during their routine practice. However, those utilizing standard screening tools to determine alcohol misuse was low (22.8%; n=75). Though the proportion of doctors who took steps to reduce misuse was high (80.3%; n=283), the steps that would achieve sustainable reduction were taken by only 45.9 %( n=130). "Good" overall knowledge (p<0.001), working in a medical unit (p<0.001), work experience <10 years (p<0.001), were associated with "always inquiring" into alcohol habits in routine practice while "Good" overall knowledge (p<0.001), being a house officer (p<0.001) and work experience <10 years (p<0.001) were associated with taking steps to reduce misuse. Conclusion and Recommendations Overall knowledge was found to be "Good". Gaps in practice of screening and management were evident, which need to be corrected. DOI: http://dx.doi.org/10.4038/jccpsl.v15i1.4936 Journal of the College of Community Physicians of Sri Lanka Vol.15(1) May 2010 24-32